Fuzzy modelling for reboiler system - Yusof, Rubiyah; Ibrahim, Mohd. Faisal; Khalid, Marzuki (2002)
Fuzzy system's ability of providing both heuristic knowledge with quantitative and accurate representation has been exploited for identification of nonlinear and complex system. Takagi-Sugeno (TS) Fuzzy System is one of the most popular method used for fuzzy modelling of multi input multi output (MIMO) dynamical system. In this paper, we propose an automatic tuning methods of fuzzy sets for TS fuzzy models using genetic algorithms. The effectiveness of the approach is illustrated by applying the method to a reboiler of batch distillation column. The results show that the proposed system gives a more accurate model than the conventional TS fuzzy model.